Pemikiran Immanuel Kant tentang Kritisisme dan Implementasinya dalam Pendidikan Islam - Farah Syafirna; Jihan Faeruzia Haris; Atika Najwa; Muhammad Faqih Khamimi (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2023)
This research aims to find out the figures of philosophers in the world of education, especially Islamic education. In this case we have the task of analyzing Immanuel Kant's thinking (criticism). This research uses research methods on selected references by taking into account the opinions of other figures regarding Kant's policies or thoughts. Immanuel Kant was a German philosopher who was considered one of the most influenced modern European thinkers, as well as the last philosopher in the Age of Enlightenment. He prioritized criticism. which can open or change other people's principles and thoughts about education. According to Kant, everything that happens must first be scrutinized by adjusting the existing ratios. Not with the thoughts of previous philosophers who argued that they only believed easily in the ability of reason without researching or looking directly and observing existing events. Simply put, Immanuel Kant said that if we want to believe or accept something, we must first investigate whether it can be accepted or not.